2020
DOI: 10.3390/w12113046
|View full text |Cite
|
Sign up to set email alerts
|

Change in Stream Flow of Gumara Watershed, upper Blue Nile Basin, Ethiopia under Representative Concentration Pathway Climate Change Scenarios

Abstract: Climate change plays a pivotal role in the hydrological dynamics of tributaries in the upper Blue Nile basin. The understanding of the change in climate and its impact on water resource is of paramount importance to sustainable water resources management. This study was designed to reveal the extent to which the climate is being changed and its impacts on stream flow of the Gumara watershed under the Representative Concentration Pathway (RCP) climate change scenarios. The study considered the RCP 2.6, RCP 4.5,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
4
9
0
1
Order By: Relevance
“…The result obtained under all the scenarios considered in this study have shown increasing trend. This result agrees with different studies made by other researchers in Ethiopian catchments (IPCC 2014, Asnake et al , 2020; Gashaw et al , 2020; Selam et al , 2020).…”
Section: Resultssupporting
confidence: 93%
“…The result obtained under all the scenarios considered in this study have shown increasing trend. This result agrees with different studies made by other researchers in Ethiopian catchments (IPCC 2014, Asnake et al , 2020; Gashaw et al , 2020; Selam et al , 2020).…”
Section: Resultssupporting
confidence: 93%
“…The SWAT model is a continuous, semi-distributed, and process-based model that is operated on a daily basis at the basin scale [33,34]. It is widely used to simulate hydrological processes on various scales, including small catchments and large catchments, under different climate scenarios over a long period of time and is especially suitable for African river basins [35,36].…”
Section: Swat Hydrological Modelmentioning
confidence: 99%
“…Therefore, the inhabitants of the Gumera watershed should use irrigation and they must manage their water resources carefully during the periods from 2011-2040 and 2041-2070. Another study revealed that, due to climate change, the streamflow of the watershed was found to increase by 4.06%, 3.26%, and 3.67% under RCP 2.6, RCP 4.5 and RCP 8.5 scenarios, respectively [1]. The temperature and sediment load are shown to increase in the future while the rainfall and streamflow decrease [2].…”
Section: Resultsmentioning
confidence: 99%
“…Climate change is the greatest threat to agriculture and food security in the 21 st century, particularly in many of the poor, agriculture-based countries of sub-Saharan Africa (SSA) with their low capacity to effectively cope [1]. Slight rises in temperatures will lead to greater loss of moisture, exacerbating drought, and desertification [2].…”
Section: Introductionmentioning
confidence: 99%